Meningkatkan Hasil Belajar IPA melalui Pembelajaran Kooperatif Tipe STAD pada Siswa Kelas V SDN 2 Panjang Utara Bandar Lampung - Jusnilawati, Jusnilawati (STKIP PGRI Bandar Lampung, 2022)
The purpose of this study is to describe the STAD type cooperative learning method can improve science learning outcomes for fifth grade students of SD Negeri 2 Panjang Utara Bandar Lampung. The research method applied is Classroom Action Research which is carried out with reference to: planning, implementation, observation, and reflection for 3 cycles. The research subjects for the fifth grade students of SDN 2 Panjang Utara Bandar Lampung for the 2019/2020 academic year were 29 people. Based on the results of the study, it was found that the science learning of Grade V students of SDN 2 Panjang Utara Bandar Lampung for the academic year 2019/2020 through Cooperative Learning of the Stad type increased.